Forest Insects and Pathogens in a Changing Environment: Ecology, Monitoring & Genetics (IUFRO Joint Meeting of WP7.03.05 & 7.03.10) - Avtzis, Dimitrios N. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
After the successful conclusion of the Joint Meeting of IUFRO's 7.03.05 & 7.03.10 working parties and given the exciting and novel studies that have been presented in the framework of this meeting, we decided to present some of these studies in the current Special Issue of Forests. To make this issue more appealing and interesting to everyone in the field of Forest Protection, studies that cover a wide range of topics were selected, ranging from ecology and phylogeography to forest management and protection. More importantly, as these studies refer to pests and pathogens from different parts of the world, it is expected that the knowledge gained can be further used in the protection of natural environment worldwide.